Relationship between TQM elements and organizational performance: An empirical study of manufacturing sector of Pakistan - Masood Ul Hassan; Saad Hassan; Sadia Shaukat; Muhammad Saqib Nawaz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
This study empirically reveals the influence of the TQM elements comprising leadership, people management, process management, customer focus, information & analysis and strategic planning on the organizational performance in the manufacturing sector of Pakistan. The data were collected through a questionnaire survey from the 160 managers and employees of the manufacturing firms. Results using SPSS support the hypotheses that there is a positive relationship between the TQM elements and performance of Pakistani manufacturing firms. Furthermore, it is also found that customer focus is perceived as a dominant TQM practice for enhancing quality performance. Moreover, this study also provides a valuable knowledge to the top managers. Practical implementations along with the limitations have also been discussed in this study.
Keywords: 330; Total Quality Management (TQM); leadership; Pakistan; organizational performance; people management